MODEL PEMBELAJARAN PAI INTERAKTIF DAN KONTEKSTUAL: STRATEGI MEMBANGUN KARAKTER MURID - Ali Wafa; Umar Faruq; Moh. Rois; Ridwan (STAI Ma'had Aly Al-Hikam Malang, 2025)
Islamic Religious Education plays a significant role in shaping students' character with good morals, both in terms of spiritual piety and social character. The interactive and contextual PAI learning model serves as an alternative for character building among students. This article employs a qualitative approach with a type of library research. Through library research, this article aims to conduct an in-depth analysis of various relevant literatures, such as books, scholarly journal articles, and other documents related to the researched topic. There are two types of data sources in this article: primary and secondary. Primary data is derived from books and journal articles that specifically discuss interactive and contextual PAI learning models as well as strategies for strengthening students' character. Secondary data includes scientific works, proceedings, research reports, and other supporting documents that enrich the understanding of the discussed topic. This article presents findings on interactive and contextual PAI learning models for building students' character, which include: the understanding model through experience, the understanding model through habituation, the understanding model through exemplary, and the contextual learning model.